The effect of road on medium-to large-sized terrestrial mammals in Kubah National Park investigated using camera trapping - Woo Chee, Yoong (Universiti Malaysia Sarawak, 2017)
Kubah National Park is famous for its numerous hiking trails with spectacular summit view point, waterfall and different kind of species of frogs at the Frog Pond as its main attractions. However, the fauna in the national park especially medium- to large-sized mammals are lack of documentation and research. Thus, a camera trap survey was conducted throughout October 2016 to April 2017 where 20 camera traps were deployed. The result obtained from a total of 191 camera nights and 2161 camera efforts was 26 species included ayes and mammals, where 19 of them were medium- to large-sized mammals. One species is listed as Critically Endangered, four as Vulnerable and two as Near Threatened based on IUCN red List of Threatened Species. Road effect based on five different distances from road in Kubah National Park was found to have no significant difference in terms of mean species richness. Occupancy and detection were analysed using five covariates which were 0 - 5 m, 5 - 100 m, 100 - 200 m, 200 - 300 m and 300 - 400 m. The result of species occupancy analysis showed that Trichys fasciculata had the highest record of Naive occupancy estimate. Analysis of activity pattern was conducted for species with independent events of n>20 with 30 minutes interval. Hemigalus derbyanus, Tragulus kanchil and Trichys fasciculata were found to be nocturnal and tend to appear on road during midnight to avoid contact with human. This research will help to access the effect of infrastructure on medium- to large-sized mammals and emphasize on future conservation in Kubah National Park.